Effect of Foot Strengthening Exercises in Osteoarthritis Knee - Cynthia S. Jagtap1 , Mandar Malawade2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Knee osteoarthritis is one of the leading cause of global disability. Patients with degenerative knee osteoarthritis clinically complain of pain, decreased muscle strength, joint instability, joint stiffness and proprioceptive deficits, all of which lead to a decrease in or loss of function. Foot pain is highly disabling, functional abilities and increases the risk of falls. Method: This was an experimental study with total of 33 subjects who had knee osteoarthritis with foot disability. Subjects of both genders with age group of 40 – 65 years fulfilling the inclusion and exclusion criteria participated. The outcome measure used was womac scale, for pain Visual analogue scale (VAS). Result:Statistical analysis of VAS, WOMAC and range of motion (ROM) were found to be extremely significant with a P value of <0.0001. Conclusion: This study concluded that foot strengthening exercises were effective. It is proved from this study that foot strengthening exercises has significant effect on pain, range of motion and functional status of OA knee.